Cooperative Reductive Elimination: The Missing Piece in the Oxidative‐Coupling Mechanistic Puzzle. (25th January 2016) - Funes‐Ardoiz, Ignacio; Maseras, Feliu
Abstract: The reaction between benzoic acid and methylphenylacetylene to form an isocoumarin is catalyzed by Cp*Rh(OAc)2 in the presence of Cu(OAc)2 (H2 O) as an oxidant and a leading example of oxidative‐coupling reactions. Its mechanism was elucidated by DFT calculations with the B97D functional. The conventional mechanism, with separate reductive‐elimination and reoxidation steps, was found to yield a naphthalene derivative as the major product by CO2 extrusion, contradicting experimental observations. The experimental result was reproduced by an alternative mechanism with a lower barrier: In this case, the copper acetate oxidant plays a key role in the reductive‐elimination step, which takes place through a transition state containing both rhodium and copper centers. This cooperative reductive‐elimination step would not be accessible with a generic oxidant, which, again, is in agreement with available experimental data.